Gut-flora metabolites is not associated with synchronous carotid artery plaque and non-alcoholic fatty liver disease in asymptomatic adults: A STROBE-compliant article. Issue 34 (27th August 2021) - Lin, Ying-Chun; Wang, Horng-Yuan; Kuo, Yang-Che; Chen, Ming-Jen; Wu, Ming-Shiang; Liu, Chun-Jen; Yang, Horng Woei; Shih, Shou-Chuan; Yu, Lo-Yip; Ko, Hung-Ju; Yeh, Hung-I; Hu, Kuang-Chun
Abstract : Abstract: Synchronous non-alcoholic fatty liver disease (NAFLD) and carotid artery plaque formation increase the risk of mortality in patients with cardiovascular disease (CVD). Metabolic status and host gut flora are associated with NAFLD and CVD, but the risk factors require further evaluation. To evaluate the risk factors associated with NAFLD and CVD, including gut-flora-related examinations. This cross-sectional study included 235 subjects aged over 40 years who underwent abdominal ultrasound examination and carotid artery ultrasound examination on the same day or within 12 months of abdominal ultrasound between January 2018 and December 2019. All subjects underwent blood tests, including endotoxin and trimethylamine-N-oxide. The synchronous NAFLD and carotid artery plaque subjects had a higher proportion of men and increased age compared with those without NAFLD and no carotid artery plaque. The synchronous NAFLD and carotid artery plaque group had increased body mass index (BMI), blood pressure, hemoglobin A1C (5.71% vs 5.42%), triglyceride (TG) (164.61 mg/dL vs 102.61 mg/dL), and low-density lipoprotein (135.27 mg/dL vs 121.42 mg/dL). In multiple logistic regression analysis, increased BMI, mean systolic blood pressure, and TG > 110 mg/dL were independent risk factors for synchronous NAFLD and carotid artery plaque formation. Endotoxin and trimethylamine-N-oxide levels were not significantly different between the 2 groups. Host metabolic status, such as elevated BMI, TG, and systolic blood pressure, are associated with synchronous NAFLD and carotid artery plaque in asymptomatic adults. Aggressive TG control, blood pressure control, and weight reduction are indicated in patients with NAFLD.